Evaluating temperature and precipitation extremes under 1.5°C and 2.0°C warming above pre-industrial levels: Botswana case study - Nkemelang, Tiro (Department of Environmental and Geographical Science, 2019)
The United Nations Framework Convention on Climate Change (UNFCCC) noted the need and therefore requested further quantitative research to better inform policy on the potential impacts of further warming to 1.5 and 2.0 °C above preindustrial levels. Climate extremes are expected to become more severe as the global climate continues to warm due to anthropogenic greenhouse gas emissions. The extent to which extremes and their impacts are to change due to additional 0.5 °C warming increments at regional level as the global climate systems warms from current levels to 1.5 and then 2.0 °C above preindustrial levels need to be understood to allow for better preparedness and informed policy formulation. Having realized the lack of research on this front in Botswana, this study investigates the differentiated impacts of climate change on climate extremes under the current, 1.5 and 2.0 °C warmer climates. The dissertation analysed the projected changes in extremes using Expert Team on Climate Change Detection and Indices (ETCCDI), derived from fifth version of Coupled Model Intercomparison Project (CMIP5) projections over Botswana, a country highly vulnerable to the impacts of climate change. Results indicate that (i) projected changes in temperature extremes are significantly different at the three levels of global warming, with hot day and night extremes expected to realise the greatest increases; (ii) drought related indices are also significantly different, and suggest progressively increasing drought risk with shortened rainfall seasons especially in northern Botswana; and (iii) heavy rainfall indices are likely to increase, but are not statistically different at the different global warming levels. The implications of these changes for key socio-economic sectors are explored, and reveal progressively severe impacts, and consequent adaptation challenges for Botswana as the global climate warms from its present temperature to 1.5 and then 2.0 °C.